Altitude influences thermal ecology and thermal sensitivity of locomotor performance in a toad-headed lizard. (January 2018) - Wu, Qiong; Dang, Wei; Hu, Ying-Chao; Lu, Hong-Liang
Abstract: Population differentiation in ectotherm physiological performance may be driven by adapting to different thermal environments. In this study, we measured locomotor performance in two different altitude populations of the Qinghai toad-headed lizards ( Phrynocephalus vlangalii ) at different test temperatures to assess between-population differences in thermal sensitivity of sprint speed. Low-elevation lizards ran faster than high-elevation lizards at most test temperatures. Sprint speed varied with test temperature similarly between populations, but the thermal sensitivity (performance breadth) differed significantly. Low-elevation lizards had a lower optimal temperature ( T opt ) for sprint speed and narrower performance breadth than high-elevation lizards as inferred from the thermal performance curves constructed for each individual. We also measured the body temperature of active lizards ( T b ) in the field and selected temperature ( T sel ) in the laboratory. Low-elevation lizards had a lower T sel, and less variable T b than high-elevation lizards. In both populations, T sel was lower than T opt for sprint speed, which was inconsistent with the prediction for a match between thermal preference and T opt . Our results suggest that lower thermal sensitivity and weaker locomotor ability for high-elevation lizards may be an adaptive response to the local environmental conditions (e.g., greater thermal variability, higher food availability, and lower predator pressure). Highlights: High-elevation lizards had a weaker locomotor ability but lower thermal sensitivity of speed than low-elevation ones. Reduced thermal performance sensitivity in high-elevation lizards may be related to greater body temperature variability. The optimal temperature for sprint speed did not match preferred temperature in both populations of P. vlangalii .